Friction angles at sandy beaches from remote imagery. Issue 4 (7th November 2017) - Stark, N.; McNinch, J.; Wadman, H.; Graber, H. C.; Albatal, A.; Mallas, P. A.
Abstract : The rigour of extracting friction angles, and eventually lower-bound bearing strength, in sandy beach settings through slope angles determined from digital images (visual spectrum) is explored. Digital images of topographic sand features using hand-held cameras, an unmanned aerial vehicle and a panchromatic satellite sensor are analysed to determine average slope angles using three-dimensional reconstruction. Greyscale gradients and shadows are utilised in the satellite images to extract slope estimates. The slope angles matched tilt table results of samples from the same locations at the Duck, NC, and Claytor Lake, VA, field sites. Direct shear testing of sample material suggest friction angles of ∼33° and ∼35°, respectively. The authors test a potential pathway to derive lower-bound bearing strength using these remotely sensed slope angles. Preliminary results are encouraging, but likely sensitive to the impact of moisture content, differences between the maximum and the observed slope angle and internal friction angles.